An Analysis of Grade IV Elementary Students’ Reading Comprehension Skills in Narrative Texts - Fajrianti, Rafni; Musthafa, Bachrudin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The present study aims to analyze the reading comprehension skills of the students of SDN 202 Suryalaya Bandung. The investigated indicators include to know main ideas, to figure out important messages and information within the text, to find facts and opinions, and to draw conclusions in the narrative text. This is a descriptive study employing the qualitative approach. The test and interviews were used as the data collection methods. The grade IV students were selected as the research subjects, with a sample of 6 students consisting of 2 high-skilled students, 2 medium-skilled students, and 2 low-skilled students. The results indicate that the high-skilled students have no difficulty reaching the specified indicators, while the medium-skilled experience some difficulties and confusion in reaching several indicators including to figure out messages in the text, to find opinions, and to draw conclusions. Meanwhile, the low-skilled have difficulties achieving the reading comprehension skills indicators because some of them have not been able to read well and also experience difficulties in understanding the provided problems